Enhancing RF-to-DC conversion efficiency of wideband RF energy harvesters using multi-tone optimization technique. Issue 2 (3rd December 2014) - Kuhn, Véronique; Seguin, Fabrice; Lahuec, Cyril; Person, Christian
Abstract : In this paper, a 1.8–2.6 GHz wideband rectenna is designed for radio frequency (RF) energy harvesting in the context of wireless sensor nodes (WSN). To assess the feasibility of ambient RF energy harvesting, the power density from RF base stations is analyzed through statistical measurements. Power density measurements are also performed close to Wi-Fi routers. Using these results, a methodology based on impedance matching network adaptation and maximum power transfer is proposed to design the wideband RF harvester. Using this method, three RF bands, i.e. GSM1800, UMTS and WLAN, are covered. The theoretical analysis is confirmed by simulations and measurements. From measurements results, the prototype RF-to-DC conversion efficiency is 15% at −20 dBm from 1.8 to 2.6 GHz. It is shown that with three RF sources in the chosen bands, each emitting at 10 dBm, the RF-to-DC conversion efficiency is 15% better compared to that measured with a single RF source. Finally, 7 µW is harvested at 50 m from a GSM1800 and UMTS base station. This value confirms the RF harvester workability to supply small sensors.